X Chromosome Dose and Sex Bias in Autoimmune Diseases: Increased Prevalence of 47, XXX in Systemic Lupus Erythematosus and Sjögren's Syndrome. Issue 5 (May 2016) - Liu, Ke; Kurien, Biji T.; Zimmerman, Sarah L.; Kaufman, Kenneth M.; Taft, Diana H.; Kottyan, Leah C.; Lazaro, Sara; Weaver, Carrie A.; Ice, John A.; Adler, Adam J.; Chodosh, James; Radfar, Lida; et al.
Abstract : Objective: More than 80% of autoimmune disease predominantly affects females, but the mechanism for this female bias is poorly understood. We suspected that an X chromosome dose effect accounts for this, and we undertook this study to test our hypothesis that trisomy X (47, XXX; occurring in ∼1 in 1, 000 live female births) would be increased in patients with female‐predominant diseases (systemic lupus erythematosus [SLE], primary Sjögren's syndrome [SS], primary biliary cirrhosis, and rheumatoid arthritis [RA]) compared to patients with diseases without female predominance (sarcoidosis) and compared to controls. Methods: All subjects in this study were female. We identified subjects with 47, XXX using aggregate data from single‐nucleotide polymorphism arrays, and, when possible, we confirmed the presence of 47, XXX using fluorescence in situ hybridization or quantitative polymerase chain reaction. Results: We found 47, XXX in 7 of 2, 826 SLE patients and in 3 of 1, 033 SS patients, but in only 2 of 7, 074 controls (odds ratio in the SLE and primary SS groups 8.78 [95% confidence interval 1.67–86.79], P  = 0.003 and odds ratio 10.29 [95% confidence interval 1.18–123.47], P  = 0.02, respectively). One in 404 women with SLE and 1 in 344 women with SS had 47, XXX. There was an excess of 47, XXX among SLE and SS patients. Conclusion: The estimated prevalence of SLE and SS in women with 47, XXX was ∼2.5 and ∼2.9 times higher, respectively, than that in women with 46, XX and ∼25 and ∼41 times higher, respectively, than that in men with 46, XY. No statistically significant increase of 47, XXX was observed in other female‐biased diseases (primary biliary cirrhosis or RA), supporting the idea of multiple pathways to sex bias in autoimmunity.